LANGKAH STRATEGIS TIONGKOK DALAM NORMALISASI HUBUNGAN ARAB SAUDI-IRAN DI TIMUR TENGAH - Nashir, Asep Kamaluddin (Universitas Jenderal Ahmad Yani, 2024)
This paper aims to analyze China's strategic moves to achieve mutual concession in the issue of normalizing relations between Saudi Arabia and Iran. Furthermore, this paper explains the change from enmity to friendship between Saudi Arabia and Iran, explaining China's strategic foreign policy moves in the Middle East. The concepts of foreign policy, diplomatic bargaining, and enmity-amity are used to analyze the issues raised in this paper. Certain international reports and analyses, as well as some official documents and literature, will be obtained to collect some data to provide an overview of the focus of the analysis as described by qualitative research focusing on literature study. The main findings in this analysis explain that foreign policy supported by economic capabilities has encouraged China's foreign policy to expand the scope of partnerships that affect economic, political, and security developments in the Middle East through the stages of diplomacy to improve China's bargaining position. This not only provides space for China to contribute to the Middle East but also at the same time provides China with space to expand its influence while increasing the competitive side in the competition between China and the US in the Middle East. The results of this paper emphasize the need of a foreign policy direction that in line with the national interests and supported by diplomatic skills is needed to increase the role and global contribution regarding the national strategic interest.